Analisis Linear Programming dengan Metode Simpleks untuk Memaksimalkan Keuntungan pada UD Sumberwaras di Karanganyar - Anissa Nur Azizah; Erni Widajanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is an analysis of maximizing profits at UD SUMBERWARAS using a simplex method linear programming analysis tool via the POM QM for Windows V5 application and carrying out manual calculations. The type of data used in this research is qualitative and quantitative data. The results obtained are H1 which states